1999
DOI: 10.1017/s1368980099000531
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, diet and skeletal health

Abstract: Diet and physical exercise concur in the determination of skeletal mass at the end of adolescence and in the conservation of it during adult life. The functional demand imposed on bone is a major determinant of its structural characteristics. Stress applied to a skeletal segment affects the geometry of the bone, the microarchitecture and the composition of the matrix. The stimulatory effect occurs when the skeleton is subjected to strains exceeding habitual skeletal loads, and the intensity of load is more imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 48 publications
0
18
1
1
Order By: Relevance
“…Higher levels of activity are associated with reduced risks of coronary heart disease (Batty, 2002), stroke (Wendel-Vos, Schuit, Feskens, Boshuizen, Verschuren, Saris et al, 2004), diabetes (Jeon, Lokken, Hu & van Dam, 2007), various cancers (e.g. Tardon, Lee, DelgadoRodriguez, Dosemeci, Albanes, Hoover et al, 2005;Monninkhof, Elias, Vlems, van der Tweel, Schuit, Voskuil et al, 2007) and improved skeletal health (Branca, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of activity are associated with reduced risks of coronary heart disease (Batty, 2002), stroke (Wendel-Vos, Schuit, Feskens, Boshuizen, Verschuren, Saris et al, 2004), diabetes (Jeon, Lokken, Hu & van Dam, 2007), various cancers (e.g. Tardon, Lee, DelgadoRodriguez, Dosemeci, Albanes, Hoover et al, 2005;Monninkhof, Elias, Vlems, van der Tweel, Schuit, Voskuil et al, 2007) and improved skeletal health (Branca, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of activity are associated with reduced risks of coronary heart disease (Batty, 2002), stroke (Wendel-Vos, Schuit, Feskens, Boshuizen, Verschuren, Saris et al, 2004), diabetes (Jeon, Lokken, Hu & van Dam, 2007), various cancers (e.g. Tardon, Lee, DelgadoRodriguez, Dosemeci, Albanes, Hoover et al, 2005;Monninkhof, Elias, Vlems, van der Tweel, Schuit, Voskuil et al, 2007) and improved skeletal health (Branca, 1999).Evidence for these and other health benefits has been extensively reviewed in the United States by the Physical Activity Guidelines Advisory Committee (2008), which concluded that there was very strong evidence linking physical activity to better health-related fitness, lower risk of developing disabling medical conditions and lower rates of various chronic diseases.Increasing physical activity is a medical recommendation and a public health policy objective (e.g. World Health Organization, 2002).…”
mentioning
confidence: 99%
“…However, E2 has also been associated with enhanced breast and uterus carcinogenesis. Interest in soy and soybean constituents is driven primarily by reported potential health benefits in a variety of areas, including the prevention of cancer (Cross et al 2004) and osteoporosis, improvement of bone health (Branca 1999, 2003, Branca & Lorenzetti 2005, and a lowered risk of cardiovascular diseases (Cos et al 2003, Dixon 2004, Valachovicova et al 2004, Beck et al 2005. Their estrogenic activities may play an important role in their health-enhancing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity among adults has been associated with decreased risk of obesity, 1 coronary heart disease, 2,3 non-insulin-dependent diabetes mellitus, 4 osteoporosis, 5 and certain types of cancer, especially colon cancer. 6,7 Studies also show an inverse association between physical activity and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%